Production and quality of mini watermelon cv. Smile irrigated with saline water - Alan B. O. de Sousa; Sérgio N. Duarte; Osvaldo N. de Sousa Neto; Ana C. M. Souza; Pedro R. F. Sampaio; Carlos T. dos S. Dias (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The purpose of this study was to evaluate the salt tolerance of mini watermelon (cv. Smile). The experiment was carried out in the greenhouse of the Department of Biosystems Engineering of ESALQ/USP. The experimental design was randomized blocks. The plants were irrigated with five levels of salinity (S1 = 1.0; S2 = 2.0; S3 = 3.0; S4 = 4.0 and S5 = 5.0 dS m-1). At 85 days after the beginning of the experiment, the plants and the physical and chemical variables of the fruit were evaluated. Salinity negatively affected the variables: length of the main stem, stem diameter, number of leaves, number of branches, leaf area, fresh and dry matter. Regarding the physical and chemical characteristics of fruits, salinity reduced the mass, diameter and the pH of the fruit, but increased its vitamin C content. In general, the results suggest that the mini watermelon (cv. Smile) is moderately sensitive to salinity.